Fixed-bed adsorption of metal ions from aqueous solution on polyethyleneimine-impregnated palm shell activated carbon - Yin, C.Y.; Aroua, M.K.; Daud, W.M.A.W. (Elsevier, 2009)
Fixed-bed adsorption studies with virgin and polyethyleneimine (PEI)-impregnated palm shell activated carbon (AC) as a media for the removal of single Ni2+ or Cu2+ ions from aqueous solution were conducted. The studies were conducted in a vertical down flow Perspex column with influent pH at 5 with either Ni2+ or Cu2+ had an influent concentration of 1 mmol/L. The adsorption data were fitted to three-well-established fixed-bed adsorption models, namely, bed-depth-service-time (BDST), Thomas and Yoon-Nelson models. It was observed that PEI impregnation at 8.41 wt had increased the breakthrough volume and service time of AC by factors of 2.1 (Cu2+) and 1.6 (Ni2+) as compared to virgin AC. For Cu2+ adsorption, the modelled BDST, Thomas and Yoon-Nelson curves were in very good agreement with the experimental curves while it was conversely true for Ni2+ adsorption. Â© 2008 Elsevier B.V. All rights reserved.